2020
DOI: 10.1002/jcph.1692
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Knowledge Gaps in Assessment and Management of Severe Drug Hypersensitivity Reactions: Multicenter Cross‐Sectional Study of Australian Health Care Providers

Abstract: Severe drug hypersensitivity reactions (DHRs) are often encountered by health care professionals (HCPs). We evaluated knowledge of doctors and pharmacists in the assessment and management of severe DHRs using a structured questionnaire. A cross-sectional study was conducted in 4 metropolitan hospital networks in Melbourne, Australia. A 13-question, scenario-based multiple-choice questionnaire to assess specific knowledge domains in drug hypersensitivity syndrome recognition, causality attribution, cross-reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…Many studies have examined the reasons behind underreporting, yet few studies have evaluated variations in the quality of ADR reports, and risk communication. The latter two factors are more likely influenced by HCPs' knowledge and skills [48]. Thus, overall clinical competency may significantly contribute to variations in management observed [49].…”
Section: Sources Of Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have examined the reasons behind underreporting, yet few studies have evaluated variations in the quality of ADR reports, and risk communication. The latter two factors are more likely influenced by HCPs' knowledge and skills [48]. Thus, overall clinical competency may significantly contribute to variations in management observed [49].…”
Section: Sources Of Variationmentioning
confidence: 99%
“…In the same survey, over 95% believed pharmacovigilance teaching should be included in the undergraduate pharmacy curriculum and almost 90% believed that professional bodies should include this topic in postgraduate professional development activities [57]. Specifically on the knowledge regarding drug hypersensitivity reactions (DHRs), an Australian multicentre study amongst 238 medical doctors and pharmacists surveyed in hospital settings found significant knowledge gaps in the domains of syndromic recognition, causality attribution, antibiotic cross-reactivity patterns and diagnostics/therapy, corresponding to an overall correct score of just 55.6% [48]. Knowledge gaps were similar for key ADR principles assessed, regardless of healthcare profession and seniority level [48].…”
Section: Knowledge Gaps In Adr Assessment and Reportingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent literature suggests that physicians and pharmacists possess significant knowledge gaps related to the management of antibiotic allergies. 14-16 De Clercq et al assessed family physicians and pharmacists and found that participants believed they had insufficient knowledge about antibiotic allergies, and many were unaware of negative health consequences associated with antibiotic allergies. 14 A survey on inpatient practitioners by Staicu et al found that the majority of respondents reported spending less than 2 minutes assessing patients’ allergy histories.…”
Section: Introductionmentioning
confidence: 99%
“…15 Mazzoni et al assessed providers on knowledge related to drug hypersensitivity, with only 55.6% providing correct responses. 16…”
Section: Introductionmentioning
confidence: 99%